Chronoamperometry of Some Substituted Phenacyl Bromides - Mastan Rao, K.; Jayarama Reddy, S. (Asian Journal of Chemistry, 2010)
Chronoamperometry of substituted phenyl bromide like p-phenyl,p-methyl, p-methoxy and m-methoxy phenacyl bromide has been studied under hanging mercury drop electrode (HMDE) in 50% (v/v) ethanol-water mixtures. Adsorption phenomena are characterised from it1/2 vs. t plots and diffusion coefficient and forward rate constant values have been evaluated at specific step potentials.